An investigation into the accessibility of web-based information for people with dementia - Savitch, Nada; Zaphiris, Panayiotis (My University, 2005)
People with dementia have problems with memory, attention, language and orientation. Designers in the physical environment have started to consider the needs of people with dementia, but research into the use of computers by people with dementia has not been widespread. The large English-speaking Alzheimers associations around the world are all committed to providing information for people with dementia via their websites. However, analysis of the websites indicates that the pages may not have been designed specifically for people with memory and language problems in mind. A small scale preliminary evaluation of four Alzheimers association websites from across the world demonstrated that people with dementia can contribute to the design of websites. The location of the link from the home page to information specifically for people with dementia is of particular importance.